2022
DOI: 10.1161/hypertensionaha.121.18284
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Imaging-Guided Adrenalectomy in Young Patients With Primary Aldosteronism

Abstract: Many of the patients with primary aldosteronism (PA) are denied curative adrenalectomy because of limited availability or failure of adrenal vein sampling. It has been suggested that adrenal vein sampling can be omitted in young patients with a unilateral adrenal nodule, who show a florid biochemical PA phenotype. As this suggestion was based on a very low quality of evidence, we tested the applicability and accuracy of imaging, performed by computed tomography and/or magnetic resonance, for identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 33 publications
0
22
0
2
Order By: Relevance
“…However, it should be acknowledged that the study was underpowered for its primary endpoints [71,72]. Moreover, in the AVIS-2 Imaging study [73] 34 % of PA submitted to AVS had negative imaging and 7 % had bilateral nodules, thus raising serious concerns about an imaging-only-based strategy for identifying surgically curable PA.…”
Section: Issues In the Diagnostic Work-up Of Primary Aldosteronism In...mentioning
confidence: 99%
“…However, it should be acknowledged that the study was underpowered for its primary endpoints [71,72]. Moreover, in the AVIS-2 Imaging study [73] 34 % of PA submitted to AVS had negative imaging and 7 % had bilateral nodules, thus raising serious concerns about an imaging-only-based strategy for identifying surgically curable PA.…”
Section: Issues In the Diagnostic Work-up Of Primary Aldosteronism In...mentioning
confidence: 99%
“…Hypertensive patients with serum potassium 3.5 mmol/l, PAC at least 20 ng/dl, PRC 5 mIU/ml or less could also be considered for bypassing of confirmatory testing, as our previous study found this set of criteria to have a specificity of 97% in making the diagnosis of primary aldosteronism [27]. Hypokalemia was found in a subset of primary aldosteronism patients, 48-88% of patients with UPA and 17-56% of patients with BPA [3][4][5] but it was the most commonly used predictor of UPA in previously published predictive models [1,15,[17][18][19]21,22,37]. Some studies found that hypokalemia had the best predictive power among the indicators [16,20].…”
Section: Diagnosing Unilateral Primary Aldosteronismmentioning
confidence: 99%
“…The Endocrine Society Guidelines recommend that for young patients (age <35 years) with spontaneous hypokalemia, marked aldosterone excess, and unilateral adrenal lesions with radiological features consistent with a typical adenoma (>10 mm) on adrenal CT may bypass AVS and proceed to unilateral adrenalectomy [1] as CT and AVS results are concordant in this patient group [11,14]. Recently, a multicenter study reported that a unilateral nodule and hypokalemia could be used to identify unilateral primary aldosteronism in patients 45 years or less of age [15]. However, in large prevalence studies from around the world, the average age of diagnosis of UPA was 47-49 years [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta‐analysis and a prospective cohort study favour surgical treatment over mineralocorticoid receptor antagonists to reduce cardiovascular events and mortality in unilateral PA, 9,10 but rigorous subtype classification is essential when considering adrenalectomy as a possible treatment. Anatomical imaging with adrenal computed tomography or magnetic resonance imaging has not proven sufficient sensitivity or specificity in most cases but may guide the treatment in young patients with clear PA, hypokalaemia and a solitary nodule 11–14 . However, adrenal venous sampling (AVS), the gold standard method for lateralization diagnosis, poses methodological challenges 11,15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical imaging with adrenal computed tomography or magnetic resonance imaging has not proven sufficient sensitivity or specificity in most cases but may guide the treatment in young patients with clear PA, hypokalaemia and a solitary nodule. [11][12][13][14] However, adrenal venous sampling (AVS), the gold standard method for lateralization diagnosis, poses methodological challenges. 11,15,16 Previous reports suggested that functional imaging with 11 C-metomidate positron emission tomography ( 11 C-MTO-PET) offers an alternative to AVS for PA subtype classification, [17][18][19] but in our recent prospective study, 20 11 C-MTO-PET was inferior to AVS.…”
Section: Introductionmentioning
confidence: 99%